A study on the relationship between employees' benefits and employees' work productivity at the national energy University (UNITEN), Campus Sultan Haji Ahmad Shah (KSHAH) / Nur Syamimi Sulaiman - Sulaiman, Nur Syamimi (Faculty of Business and Management, 2018)
The purpose of this research to identify the type of employees' benefits that employees need the most. Besides that, this research was conducted to determine the relationship between employees' benefits and employees' work productivity. To obtain the result for this research, this research was conducted among staff in The National Energy University (UNITEN), Campus Sultan Haji Ahmad Shah, Pahang. The 53 questionnaires were distributed as the methods to collect the data for this research. Simple Random Technique has been selected in this research. The research objectives of this study were achieved and research questions were answered. The conclusion and recommendation for this study were proposed. The recommendation involves for organization, employees and future research. The future researcher can be aware about the employees' benefits and employees' work productivity.